Peran Pemerintah Desa dalam Pengelolaan Sampah Perspektif Peraturan Daerah Nomor 2 Tahun 2015 Tentang Pengelolaan Sampah - Tamrin Muchsin; Sri Sudono Saliro (Law Department, Sharia and Law Faculty., 2020)
The purpose of this study was to determine the role of the Sepuk Tanjung Village Government in waste management, and to determine the inhibiting factors for implementing the government's role. When the amount of waste increases, it will cause problems that can endanger humans, both health and the environment. Therefore, it is important to involve the village government as the government that is closest to the people. This research method uses empirical research methods with a statutory approach, to obtain data, researchers conducted observations and interviews with the village government and the community using purposive sampling. The results of the study reveal that the role of the village government is in accordance with Article 11 of Regional Regulation Number 2 of 2015 concerning Waste Management. As for the inhibiting factors, namely, the community factor, the infrastructure factor and the village government factor.